Bonjour, j'ai besoin d'aide pour cet exercice svp .

Supprime les parenthèses puis réduis les expressions suivantes :

(x=lettre)

A= (x+3) + (4x - 5)

B= 6-2t - (4t - 8)

C= - (8a + 3) - 4a

D= (3y + 7) + ( - 5y + 3)

E= 5z - 6 - (7- 2z) + 3z

F= (3 - 4x) - (- 2x + 8)

2

Réponses

  • Utilisateur Brainly
2014-03-16T17:54:20+01:00
A= (x+3) + (4x - 5)
  =5x-2

B= 6-2t - (4t - 8)

  =2t+14

C= - (8a + 3) - 4a
  =-12a-3

D= (3y + 7) + ( - 5y + 3)
  =-2y+10

E= 5z - 6 - (7- 2z) + 3z
  =10z-13

F= (3 - 4x) - (- 2x + 8)
  =-2x-5
  • Omnes
  • Modérateur confirmé
2014-03-16T17:56:31+01:00
Salut,

A= (x+3) + (4x - 5)
A = x + 3 + 4x - 5
A = x - 2

B= 6-2t - (4t - 8)
B = 6 - 2t - 4t + 8
B = -6t + 14

C= - (8a + 3) - 4a
C = -8a - 3 - 4a
C = -12a - 3

D= (3y + 7) + ( - 5y + 3)
D = 3y + 7 - 5y + 3
D = -2y + 10

E= 5z - 6 - (7- 2z) + 3z

E = 5z - 6 - 7 + 2z + 3z
E = 10z - 13

F= (3 - 4x) - (- 2x + 8)

F = 3 - 4x + 2x - 8
F = -5 - 2x

Bonne journée !